Economic Innovation in Soponyono Village: VCO Production as an Alternative Cooking Oil Solution - Laila Nur Anvasa; Antomi Saregar; Adyt Anugrah (FOUNDAE (Foundation of Advanced Education), 2023)
The increase in cooking oil prices has become a significant economic issue, considering that cooking oil is one of the strategic commodities among the nine essential goods with many uses. This outreach program aims to provide knowledge on the production of Virgin Coconut Oil (VCO) as a healthier alternative to cooking oil, while also developing the potential of coconut as a source of income for the community in Soponyono Village, Wonosobo District, Tanggamus Regency. The method used was an outreach with a direct demonstration of VCO production, starting with an experiment. This outreach involved 24 participants from the Soponyono Village community and was conducted in person. The results of this program showed that the community gained new knowledge about VCO production, as well as the ability to optimally utilize natural resources, which can improve product quality and increase its market value.